[OA169] Advanced personalised 3D dosimetry for peptide receptor radionuclide therapy based on monte carlo method. (August 2018) - Berenato, Salvatore; Grassi, Elisa; Fioroni, Federica; Finocchiaro, Domenico; Iori, Mauro; Spezi, Emiliano
Abstract : Purpose: Peptide Receptor Radionuclide Therapy (PPRT) is nowadays the most effective therapy for treating patients who suffered of neuroendocrine tumours[1] . In clinical practice, absorbed dose calculations are computed based on the Medical Internal Radiation Dose (MIRD) scheme (not planned or optimised for patients' specific characteristics). To increase the quality and the efficacy of the clinical trials, a more accurate 3D dosimetry is required. Monte Carlo (MC) techniques showed to provide the most accurate approach for the MRT dose calculations. In this work, Raydose MC based pipeline[2] was used to compute the patient specific dose calculation for a clinical trial in PRRT. The dose obtained for lesions and organs at risk (OARs) were then compared to the ones based on the MIRD scheme. Methods: One hundred patients were enrolled as part of a clinical trial in PRRT with a prescribed activity between 3.7 and 5.5 GBq of 177Lu-DOTA-Tyr3-octreotide. Patients were scanned five times with a SPECT/CT scanner and the sequential scans were co-registered using a non-rigid registration algorithm[3] . Volumes of interest (VOIs) including lesions and OARs were manually outlined on fused images. 3D dose maps calculated with Raydose were compared to the corresponding ones obtained with OLINDA/EXM software. Differences between calculations were evaluated using a paired samples Wilcoxon-Mann-Witney test (two-sided, p < 0.05). Results: Mean doses calculated with OLINDA/EXM were higher than the corresponding mean doses calculated with Raydose. In particular, for the structures studied, the following median percentage differences were obtained: kidneys, −11.70% (Internal Quartile Range (IQR) = 7.14); liver, −14.06% (IQR = 5.62); spleen, −12.50% (IQR = 6.38); lesions, −21.01% (IQR = 18.52). Furthermore, significant differences were observed for kidneys and lesions. Conclusions: Dose values obtained with the MC method suggested an underestimation of the dose calculated for OARs and lesions in PRRT treatment. A more accurate patient specific 3D dose calculation could be used to increase the injected activity and to rise the efficiency of the treatment but maintaining a safe level of toxicity.